Pengembangan Modul Matematika Berbasis Inkuiri Terbimbing Materi Bangun Datar Kelas IV SDN 12 Pangkalpinang - Novita, Novita; Fitri Apriani; Sisi Pitriyana (JBES (Journal Basic Education Skills), 2024)
This research is motivated by the lack of use of teaching materials in schools which are still not effective because the materials are instant. The aim of the research is to determine the characteristics of the Guided Inquiry-Based Mathematics Module teaching materials that are valid, practical and effective in plane material. This type of research is an ADDIE development model (Analyze, Design, Development, Implementation and Evaluation. The data collection techniques and instruments used are observation, interviews, questionnaires and tests. This research produces Guided Inquiry Based Mathematics Module teaching materials which are very valid). '', ''very practical'' and "effectiveness". This can be seen from the results of the media expert validation percentage of 87.5%, material expert validation of 90% and language expert validation of 95%. The validity of the test instrument is carried out by testing validity using SPSS 25 with the average r_count>r_tabel declared valid. Reliability of the test instrument was carried out using a reliability test using the Alpha Cronbach formula with SPSS 25 of 0.416 with the criteria "medium". Next, the results of the practicality of the Guided Inquiry Based Mathematics Module teaching materials are from the results of the response questionnaire. small-scale test students were 100%. The development of a Guided Inquiry-Based Mathematics Module stated that the effectiveness of the student learning outcomes test was 0.69 in the "medium" category.